PROOF OF THE CRIME OF SUPERNATURAL POWERS IN LAW NUMBER 1 OF 2023 AS A LEGACY OF THE WETBOEK VAN STRAFRECHT - Agung Risky Saputra Marpaung; Frans Simangunsong (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the regulation of witchcraft offenses in the National Penal Code under Law Number 1 of 2023. Witchcraft, or santet, is a supernatural phenomenon involving metaphysical forces intended to inflict physical, mental, or emotional suffering on victims. The study aims to analyze existing legal regulations and evaluate the challenges of proving such cases within Indonesia's legal system. A normative juridical method was applied, with an analysis of legal statutes and relevant legal literature. The findings indicate that Article 252 sanctions individuals claiming to possess supernatural abilities, with penalties of up to 1 year and 6 months imprisonment or a fine of Category IV, with an additional one-third penalty if the act is committed for profit. While legal provisions exist, proving witchcraft offenses remains difficult due to their intangible nature. Approaches such as expert testimony, medical evidence, and technological tools are highlighted as alternatives for improving evidence mechanisms. In conclusion, the effectiveness of legal regulations on witchcraft offenses requires strengthening evidentiary tools and adopting holistic approaches to ensure justice and legal certainty.